Wasp mimicking Monoceromyia eumenioides (Saunders, 1842) (Diptera: Syrphidae) visiting flowers of the tropical tree plant, Bridelia retusa (L.) A. Juss. from India. (2nd January 2023) - Sai Teja, Katta Subramanya; Ganiger, Prabhu
ABSTRACT: The wasp mimicking flower fly, Monoceromyia eumenioides (Saunders) is reported for the first time visiting flowers of tropical tree plant Bridelia retusa (L.) A. Juss. in April and May in Bangalore, Karnataka State India. Important identification characters of adult, male genitalia images and notes on the distribution, mimicry and its host plants are given.